Exploring the Potential of Pressure Retarded Osmosis: A Review on Case-Based Analysis of Energy Recovery Technologies - Menon, Salma Arthi (CV. Green Publisher Indonesia, 2025)
Pressure Retarded Osmosis (PRO) is a promising salinity gradient energy technology that harnesses the osmotic pressure difference between freshwater and saline sources to generate renewable energy. This paper provides a comprehensive review of the theoretical basis, thermodynamic principles, membrane technologies, and real-world applications of PRO systems. It examines case studies of hybrid implementations with seawater reverse osmosis (SWRO) and wastewater treatment facilities, focusing on energy efficiency, brine dilution, and environmental benefits. Additionally, the paper addresses critical challenges such as membrane fouling, internal concentration polarization, and system scalability. Through a systematic analysis of Scopus-indexed studies, this work identifies key technological advancements and future research directions essential for commercializing PRO technology. The findings suggest that with continued innovation and interdisciplinary collaboration, PRO can become a vital contributor to the sustainable energy mix and water resource management strategies.